Gender differences in elite Olympic distance triathlon performances - Cejuela, R.; Cortell-Tormo, J. M.; Chinchilla-Mira, J. J.; Perez-Turpin, J. A.; Villa, J. G. (Journal of Human Sport & Exercise, 2012)
To analyze the overall Olympic distance triathlon performances at elite male and female World Championship and Olympic Games events from 2000 to 2008. Time, lost time and partial position for each segment and transition, gender differences in performance for the three disciplines, and overall times of the males and females were analysed. The only significant difference between the sexes with regard to the percentage time used in the swimming segment (16.3±0.6M versus 15.6±0.6F). The gender (SD) difference in power output for the winners in swimming, cycling, running were 13.7±16.1%, 67.1±4.3%, 29.8±8.4%, respectively. The correlation coefficients between the lost time for each segment and transition, and the final overall classification were (0.4 M versus 0.48 F) for swimming, (0.28 M versus 0.3) for T1, (0.34 M versus 0.31 F) for Lost Time T1, (0.63 M versus 0.77 F) for cycling, r=0.33 (0.33 M versus 0.34 F) for T2, (0.43 M versus 0.29 F) for Lost Time T2 and (0.83 M versus 0.84 F) for running. The running segment is the most decisive, having a more obvious correlation for males because there are less breakaways or hilly segments that break up the main pack, while the level of performance is similar for most competitors. With females, performance is more varied and there are further variables that make the running segment less decisive. However, small differences in seconds that occurred in the swimming segment and transitions can have a significant impact on the outcome of the competition.